KEMAMPUAN DAYA TAHAN KARDIOVASKULER PRAJURIT TNI YANG BERTUGAS DI POS PERBATASAN INDONESIA - MALAYSIA - Dwi Mulyo Puguh Prayogo; Fitri Puspa Hidasari; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the cardiovascular endurance of Indonesian National Armed Forces (TNI) Soldiers who served at the Indonesia-Malaysia Border Post in the ranks of the Chef's Post, Sei Daun, Kab. Sanggau. The research method used is a survey and cardiovascular endurance fitness in this study was measured using the Cooper test. The subjects of this study were members of the TNI soldiers at the Indonesia-Malaysia border post in the ranks of the Sei Daun Koki Post, Kec. Sanggau. The results of the research carried out by 30 TNI soldiers and then analyzed so that the statistics in the study were obtained, namely the maximum value of 2900, the minimum value of 2300, the average of 2570, the mode of 2500, the median of 2525, and the standard deviation of 199, 41 and the good category was 63% (19 soldiers), then the medium category was 20% (6 soldiers), after that the very good category was 17% (5 soldiers), and the less or very less category had the same percentage, namely 0% ( 0 soldiers ).Keywords: Cardiovascular, Endurance Ability, Sei Daun, TNI soldiers at the chef post